STUDI PERKEMBANGAN AKTIVITAS PEREKONOMIAN PADA STRUKTUR RUANG PUSAT KOTA PALU - Muamar, Andi (Katalogis, 2017)
This research aims to find out the development economy activity on spatial structure in central Palu. This was a descriptive research with qualitative method. Analysis used was descriptive comparative functions to see the relation between aspect of spatial structure and aspect affect city economy using two periods of time 2005 and 2015. The data analysis technique would be obtained in these two periods of time. The research results indicate that economy activity developed in Palu from 2005 to 2015 was industry activity, commercial and service and settlement. The third development is economy activity that involves land convection from open space and horticulture farming to constructed space so impacted to open space quantity decrease and horticulture farming activity in the area. Land conversion that occurred change land usage pattern and road network of Palu become denser. The pattern change of land usage and road network from 2005 to 2015 showed the happening of city development in this area which affecting structure model of spatial in Palu, therefore, in needs review on spatial plans of Palu of 2010 to 2030 due to the dynamic system of city activity which is very influential on the growth of Palu.